ALS clinical research learning institutes (ALS-CRLI): empowering people with ALS to be research ambassadors. Issue 3 (2nd April 2020) - Bedlack, Richard; Pogemiller, Allison; Shefner, Jeremy; Cudkowicz, Merit; Heiman-Patterson, Terri
Abstract: Objective : Patient engagement in research is increasingly recognized as important across many countries and fields. In 2008, we conducted surveys that suggested a need for improved patient engagement in ALS research. We decided to create an ALS Clinical Research Learning Institute (ALS-CRLI) to facilitate direct interactions between researchers and people with ALS and their caregivers, toward ultimately improving engagement. Methods : Initially modeled after a similar program in Parkinson's disease, our ALS-CRLI is a multi-day collection of formal courses for people with ALS and their caregivers, moderated by clinicians, scientists and patient advocates. Previous graduates (called ALS Research Ambassadors) engage with the current class participants before, during and after the courses. Prior to the courses, Research Ambassadors serve as "mentors" to the participants, offering guidance and setting expectations. Feedback during the courses is used to change the way researchers design and advertise studies, and feedback after the courses is used to improve the agenda for subsequent ALS-CRLIs. Funding is provided by patient advocacy groups including the ALS Association and ALS Hope Foundation. Research Ambassadors are provided with ongoing mentoring and notifications about opportunities for engagement via regular teleconferences with the Northeast ALS Consortium's Patient Education and Advocacy Committee and their own Facebook page. Engagement and advocacy efforts are tracked using a tool on the Northeast ALS Consortium's website. Results and Conclusions : We have now held 15 ALS-CRLIs at various locations within the United States, resulting in over 320 graduated ALS Research Ambassadors. From these engagements, researchers have been prompted to formally include patients in the design process, to design more patient-centric trials and to create new ways to help patients find trials. Research ambassadors are improving awareness and clearing up misconceptions about participation in research, improving research availability, and helping to create more patient-centric trial designs. In addition, we are now creating an ALS-CRLI Toolkit that will facilitate ALS-CRLIs throughout the world. This will be housed on the Northeast ALS Consortium website.